2015
DOI: 10.1155/2015/861627
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Computational Methods to Predict the Risk of Rupture of Abdominal Aortic Aneurysms

Abstract: Computational methods have played an important role in health care in recent years, as determining parameters that affect a certain medical condition is not possible in experimental conditions in many cases. Computational fluid dynamics (CFD) methods have been used to accurately determine the nature of blood flow in the cardiovascular and nervous systems and air flow in the respiratory system, thereby giving the surgeon a diagnostic tool to plan treatment accordingly. Machine learning or data mining (MLD) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Examples include prior segmentation of the TOF and/or ASL dataset to enhance the vessel-to-background contrast, centerline and bifurcation prediction of the vessels, automated detection of impaired flow behavior (e.g. in stenosis) and risk of rupture in aneurysms [20][21][22][23][24]. Additionally, databases of normal vascular images as well as normal flow behavior can be used to early detect pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include prior segmentation of the TOF and/or ASL dataset to enhance the vessel-to-background contrast, centerline and bifurcation prediction of the vessels, automated detection of impaired flow behavior (e.g. in stenosis) and risk of rupture in aneurysms [20][21][22][23][24]. Additionally, databases of normal vascular images as well as normal flow behavior can be used to early detect pathological changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works suggest that simulations can be used to better predict rupture risk when incorporating WSS compared to a diameter only metric, as the interaction between AAA hemodynamics and vascular biomechanics has a stronger influence on eventual rupture (Taylor and Steinman, 2010;Canchi et al, 2015) (Figures 2I-L). A study using an in vitro model showed that AAA WSS was negatively influenced by intimal thickness (Bonert et al, 2003); the inverse correlation between WSS and wall thickness increases the risk of the rupture.…”
Section: Abdominal Aortic Aneurysmsmentioning
confidence: 99%
“…Most of the studies regarding renal artery aneurysm (RAA) are in the likes of retrospective studies (Barros et al 2014;Gates et al 2017;Wang et al 2018) or case studies (Canyiğit M et al 2015;Chandra et al 2014;Hwang et al 2011;Maughan et al 2015;Sousa et al 2017;Sultan et al 2016). The FSI study is important to understand the mechanism of rupture of aneurysm at renal artery especially in the case of wide-neck aneurysm (Canchi et al 2015). Relying solely on the diameter of the aneurysm for rupture risk assessment is not sufficient as it been claimed by many researches in other aneurysm conditions (Canchi et al 2015;Farotto et al, 2018;Rissland et al, 2009;Sharzehee et al 2018;Stergiou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The FSI study is important to understand the mechanism of rupture of aneurysm at renal artery especially in the case of wide-neck aneurysm (Canchi et al 2015). Relying solely on the diameter of the aneurysm for rupture risk assessment is not sufficient as it been claimed by many researches in other aneurysm conditions (Canchi et al 2015;Farotto et al, 2018;Rissland et al, 2009;Sharzehee et al 2018;Stergiou et al 2019).…”
Section: Introductionmentioning
confidence: 99%